Do laws promoting gender equity and freedom from violence benefit the most vulnerable?: a multilevel analysis of women’s and adolescent girls’ experiences in 15 low- and-middle-income countries - Maxwell, Lauren; Khan, Zara; Yount, Kathryn M. (Health policy and planning, 2022)
In this analysis, we assess whether laws that promote gender equity and freedom from violence are associated with a lower risk of prior-year physical and sexual intimate partner violence (IPV) among adolescent girls and adult women (AGW) and whether these laws protect more and less vulnerable AGW equally. We included all 15 countries that administered the Domestic Violence Module in a Demographic and Health Survey since 2015. The primary exposure was a validated, country-level index of laws on violence against women and girls (LoVI). A multilevel approach was used to model five forms of violence (prior-year partner physical, sexual, physical or sexual violence and prior-year non-partner physical violence or sexual violence) among ever-partnered, non-widowed adolescent girls 13-19 years (n = 6691) and women 20-49 years (n = 119 343). Across countries, partner physical violence ranged from 0% to 33% and sexual violence from 0% to 23%. Laws on marital rape, child marriage and sexual harassment were negatively associated with prior-year physical and sexual IPV for women and girls. Comprehensive domestic violence legislation was unrelated to girls’ experiences of prior-year physical or prior-year sexual IPV. No interaction was observed between LoVI component laws and a score meant to capture adolescent vulnerability. Three of the four LoVI component laws had consistent, negative associations with partner violence for girls and women, but negative associations were stronger for women than girls. Thus, while laws promoting gender equity and freedom from violence are generally protective, they may be more so for women than adolescent girls. Future research should explore the impact of gender equitable laws on women’s and adolescent girls’ experiences of violence, and countries may consider more comprehensive legal protections against violence for adolescent girls.